2015
DOI: 10.1103/physrevb.91.115126
|View full text |Cite
|
Sign up to set email alerts
|

Switchable conductivity at the ferroelectric interface: Nonpolar oxides

Abstract: We investigate theoretically the interface between a ferroelectric BaTiO 3 film and a non-polar insulating SrTiO 3 substrate. We find that thin BaTiO 3 (under 5 nm) can stabilize a non-polarized state, and an additional metastable polarized state. While the non-polarized state is insulating, for the polarized heterostructure, we discover the existence of two-dimensional charge carrier gases. In this case, the heterostructure undergoes an electronic reconstruction in order to prevent the polar catastrophe. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 80 publications
4
42
0
Order By: Relevance
“…We find that the effective tunneling barrier width is therefore reduced by about two unit cells with polarization pointing into n-SrTiO 3 . Recent experimental and theoretical studies have also found this kind of interfacial electronic reconstruction in ferroelectric oxides [17][18][19].…”
mentioning
confidence: 70%
“…We find that the effective tunneling barrier width is therefore reduced by about two unit cells with polarization pointing into n-SrTiO 3 . Recent experimental and theoretical studies have also found this kind of interfacial electronic reconstruction in ferroelectric oxides [17][18][19].…”
mentioning
confidence: 70%
“…This possibility has already been explored from first principles. [13][14][15] In Refs. 13 and 14 it was shown that the 2DEG could be manipulated with the ferroelectric polarization in symmetric KNbO 3 /ATiO 3 (A=Sr, Ba, Pb) heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…When the ferroelectric polarization increases, both charge carrier density and magnetic moment at the interface increase and reach ~1.5×10 14 When the polarization of PbTiO 3 is reversed and switched to be oriented from TiO 2 to PbTiO 3 , as shown in Figure 5(a), the ferroelectric polarization of PbTiO 3 drives a charge transfer from the interfacial region. As shown in Figure.5(b), the top of valence bands shifts above Fermi level with some empty states at the IF-TiO 2 layer and two neighboring layers (TiO 2 and PbO layer).…”
mentioning
confidence: 99%